Isolation and characterization of a protective monoclonal antibody targeting outer membrane protein (OmpA) against tuberculosis - Huoming Li; Jiahong Ji; Mengjin Qu; Xiuling Ma; You Zuo; Minghui Tang; Lingyuan Zeng; Hao Li (Microbiology Spectrum)
ABSTRACT Tuberculosis (TB) caused by Mycobacterium tuberculosis (Mtb) complex is an important zoonotic infectious disease around the world, and the One Health approach is an essential strategy for TB prevention and control. The abundant surface antigens present on the cell wall of Mtb can induce protective antibodies; however, its full characterization remains incomplete. Previous research has shown that antibodies targeting surface proteins can enhance host defense mechanisms. Therefore, identifying antigens that stimulate the production of protective antibodies is essential. In this study, we focused on a select antigen, outer membrane protein (OmpA), located on the outer membrane of Mtb. By screening for antibodies with protective effects in phagocytosis and intracellular killing in vitro, we identified a protective antibody targeting OmpA. We prepared an antibody, designated as 1E1, belonging to the IgG2b isotype, which exhibited high titers of 1:2,048,000. Further research demonstrated that antibody-induced protection was achieved by promoting opsonophagocytosis in a dose-dependent manner, enhancing phagosome-lysosome fusion, and inhibiting mycobacterial intracellular growth. These findings were corroborated in vivo, with a reduction in bacterial loads of approximately 0.7 log observed in the preventive group and almost 1.0 log in the therapeutic group of mice treated with the antibodies, compared to the negative control group. Cytotoxicity assays, animal toxicity analyses, and pharmacokinetic evaluations confirmed the safety and sustained effectiveness of the antibody in vivo. These findings indicate that OmpA can elicit protective antibodies and may serve as a treatment strategy for drug-resistant TB and a promising antigen for TB vaccine development.IMPORTANCEIn this study, we identified a protective antibody targeting the outer membrane protein (OmpA) of Mycobacterium tuberculosis. This monoclonal antibody (MAb) belongs to the IgG2b isotype and exhibits high titers of 1:2,048,000 to the antigen. The cell infection assays demonstrated that antibody protection was achieved by promoting opsonophagocytosis in a dose-dependent manner, enhancing phagosome-lysosome fusion, and inhibiting mycobacterial intracellular growth in vitro and ex vivo. Cytotoxicity assays, animal toxicity analyses, and pharmacokinetic evaluations confirmed the safety and sustained effectiveness of the antibody in vivo. Furthermore, the mAb 1E1 can reduce the organs' bacterial burdens and pathological damages in the prevention mouse model as well as the treatment models. Above all, in this study, we found a novel mAb named 1E1 with IgG2b isotype targeting OmpA can have protection against tuberculosis (TB) in mice, which may serve as a treatment strategy for drug-resistant TB and a promising antigen for TB vaccine development.